Sclerotherapy for the intraoral ranula with bleomycin: technical considerations and preliminary experience - Hong-Yu Zhang; Li-Wen Su; Huan Sun; Chao-Chen Rui; Yang Wu (BMC, 2024)
Abstract Ranula is a mucous cyst that occurs in the sublingual gland (SLG) in the floor of the mouth. It can be classified into two types based on origins: One is the the lesser sublingual gland (LSLG) in the anterior segment and the Rivini duct, which is connected to it, and the other is the greater sublingual gland (GSLG) in the posterior segment. Because of the anatomical characteristics, surgical resection of the cysts carries the risk of damaging adjacent tissues and has a high recurrence rate. Intralesional injection of sclerotherapy may be a better alternative treatment. We summarized 65 cases of ranula treated with intralesional injections of bleomycin(BML). According to the origin of the ranula, 60 cases were from the LSLG and the Rivini duct, and 5 cases were from the GSLG. The results showed that 60 cases of ranula from LSLG and Rivini ducts were 100% cured during the follow-up period. The median number of injections for all patients was 1.16. All 5 cases of ranula from the GSLG did not wholly recover. This study confirmed that BLM intralesional injection is a safe and effective treatment modality for cysts from LSLG or the ducts of Rivini rather than GSLG. Therefore, before treatment, it is necessary to determine the type and origin of the cyst by characterizing its morphology to ensure the effectiveness of the treatment.